A tetrahedral molecular cage with a responsive vertex. Issue 29 (18th June 2019) - Pattillo, Christopher C.; Moore, Jeffrey S.
Abstract : The first system to combine the orthogonality of alkyne metathesis and dynamic imine exchange is reported for the preparation of a molecular cage with a reversibly removable vertex. Abstract : Dynamic covalent chemistry (DCC) is a widely used method for the self-assembly of three-dimensional molecular architectures. The orthogonality of dynamic reactions is emerging as a versatile strategy for controlling product distributions in DCC, yet the application of this approach to the synthesis of 3D organic molecular cages is limited. We report the first system which employs the orthogonality of alkyne metathesis and dynamic imine exchange to prepare a molecular cage with a reversibly removable vertex. This study demonstrates the rational and controlled application of chemical orthogonality in DCC to prepare organic cages of expanded functionality which respond to chemical stimuli.